Effect of chromium addition on high temperature creep behaviour of titanium aluminides - 338410 Maiiyeaalagan Kanniah; Esah Hamzah (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006